Salmonella sp. and Escherichia coli Contamination on Beef from Slaughterhouse and Traditional Markets in Medan City - N. Ginting; U. Hasanah; Fais, Annisa Luthfiyah (Jurnal Peternakan Integratif, 2022)
Salmonella sp and Escherichia coli are zoonotic pathogenic bacteria that can be found on beef. The presence of bacterial contamination on meat will impact the meat quality physical and in microbiological. The environment of the slaughter area is one of the factors causing Salmonella sp and Escherichia coli contamination in beef. The study aimed to determine the presence of Salmonella sp. and Escherichia coli contamination on meat from Slaughterhouses (RPH) and Medan Traditional Markets. Sampling was taken in 4 locations; RPH, and three traditional markets: Brayan, MMTC, and Central Market. Meat samples researched from October to December 2021 at Laboratorium Balai Penguji Penyidik Penyakit Balai Veteriner Regional Wilayah I. Data analysis used Paired Sample T-Test. The positive result of Salmonella spp contamination was found one a meat samples from Brayan Market. Meanwhile, Negative results of Salmonella spp contamination were found on meat samples from Slaughterhouse, MMTC Market, and Central Market. Furthermore, Escherichia coli is also found on almost all meat samples from RPH, and traditional markets.